2015
DOI: 10.3402/tellusa.v67.25977
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of forecast error investigated with an observing system simulation experiment

Abstract: A B S T R A C TThe spectra of analysis and forecast error are examined using the observing system simulation experiment framework developed at the National Aeronautics and Space Administration Global Modeling and Assimilation Office. A global numerical weather prediction model, the Global Earth Observing System version 5 with Gridpoint Statistical Interpolation data assimilation, is cycled for 2 months with once-daily forecasts to 336 hours to generate a Control case. Verification of forecast errors using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…The forecast error will then relate to the total variance in the predicted phenomenon. The saturation of forecast error occurs most quickly at the finest scales, whereas at larger scales of motion variations are observed that have the potential for predictability at longer lead times (Hoskins, 2013;Privé and Errico, 2015;Ying and Zhang, 2017;Toth and Buizza, 2019).…”
mentioning
confidence: 99%
“…The forecast error will then relate to the total variance in the predicted phenomenon. The saturation of forecast error occurs most quickly at the finest scales, whereas at larger scales of motion variations are observed that have the potential for predictability at longer lead times (Hoskins, 2013;Privé and Errico, 2015;Ying and Zhang, 2017;Toth and Buizza, 2019).…”
mentioning
confidence: 99%
“…The above remarks concerning the challenges of calibrating AMSEAS motivate the methodology used to assess the forecast error of non-phase-locked tides in AMSEAS. In the nomenclature of numerical weather forecasting, the approach taken is a self-analysis verification or self-verification (e.g., Privé and Errico, 2015). The forecast error is measured by comparing the nowcast valid at date, T n , with a forecast previously computed on the date, T f = T n − τ , with a given lead time, τ , i.e., T f + τ = T n .…”
Section: The Amseas Ocean Forecasting Systemmentioning
confidence: 99%
“…In fact, it is only possible to separate the baroclinic tide from the barotropic tide in altimetry data because of the large separation in spatial scales between these classes of waves (Zaron, 2019). However, there is another component of sea level variability associated with the tidal frequencies that represents non-phaselocked baroclinic tides, which are created by temporal modulations of the propagation medium (Munk and Cartwright, 1966;Rainville and Pinkel, 2006;Colosi and Munk, 2006;Zilberman et al, 2011;Ray and Zaron, 2011). Because modulations of the propagation medium -caused by mesoscale eddies and other processes -are, in part, represented within operational ocean forecasting systems, it ought to be possible to predict some component of the non-phase-locked tide with such a forecasting system.…”
Section: Introductionmentioning
confidence: 99%
“…The above remarks concerning the difficulty with mapping the baroclinic tides motivate the methodology used to assess the forecast error of non-phase-locked tides in AMSEAS. In the nomenclature of numerical weather forecasting, the approach taken is a self-analysis verification, or self-verification (e.g., Privé and Errico, 2015). The forecast error is measured by comparing the nowcast valid at date, T n , with a forecast previously computed on the date, T f = T n − τ , with a given lead-time, τ , i.e., T f + τ = T n .…”
Section: Phase-locked Tides In Amseasmentioning
confidence: 99%